Problematika Klaim Asuransi pada PT. Jaminan Pembiayaan Askrindo Syariah Cabang Medan - Rizka Afriani; Yusrizal Yusrizal (Universitas Muhammadiyah Surabaya, 2023)
ABSTRACTClaims are an important aspect of underwriting. This is of course explained by the fact that this is a form of guarantee provided by the company as guarantor to the guarantor (Makful Lahu). Failure to claim claims or cancellation of Makful Lahu's right to claim claims is common. This is usually caused by submitting a claim that is not in accordance with the existing terms and conditions. For this reason, the research method used is interviews which aim to find out the factors that cause non-payment of claims or those that cause the cancellation of Makful Lahu's claim rights against claims (Ta'widh). Through this journal, it is expected to provide information regarding the disbursement of claims. This is of course to avoid or reduce the failure of claim disbursement.Â Keywords: Claims and the problem of failure to disburse claims